Polymorphic Subtyping for Effect Analysis: The Semantics - Amtoft, Torben; Nielson, Flemming; Nielson, Hanne Riis; Ammann, Jürgen (DAIMI Report Series, 1996)
We study an annotated type and effect system that integrates <kbd>let</kbd>-polymorphism, effects, and subtyping into an annotated type and effect system for a fragment of Concurrent ML. First a small step operational semantics is defined for concurrent ML and next the annotated type and effect system is proved semantically sound. This provides insights into the rule for generalisation in the annotated type and effect system.